KONSEP PEMIDANAAN TERHADAP PECANDU NARKOTIKA MENURUT UU NO 22 THN 1997 - Titik Suharti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Number Law 22 Year 1997 about Narcotic differentiate in the case of crime sanction to misuse in a state of depending and misuse a do not in depending and referred mention pecandu narcotic. Conception the crime to like a narcotic more emphasis at rehabilitating medical, rehabilitate the social and also medication. Conception the such crime have mirrored the target punish by proporsional between justice target, target of benefit and certainty target.